Neural basis of self-esteem: social cognitive and emotional regulation insights - Morio Aki; Mami Shibata; Yoshihisa Fujita; Michael Spantios; Kei Kobayashi; Tsukasa Ueno; Tsukasa Ueno; Takashi Miyagi; Sayaka Yoshimura; Sayaka Yoshimura; Sayaka Yoshimura; Naoya Oishi; et al. (Frontiers in Neuroscience)
IntroductionSelf-esteem (SE) can significantly affect individual well-being and has been linked to various psychiatric conditions. SE involves cognitive and emotional regulation within a social context. Prior research focusing on young adults has indicated neural correlations in prefrontal cortex areas but presented inconsistent findings. Our study expanded this to a broader age range and covariates, and examined the influence of subthreshold depression, emphasizing the functional role of the dorsolateral (dlPFC), ventrolateral prefrontal cortices (vlPFC) and cerebellum in social cognition and emotional regulation of social exclusion.MethodsWe conducted resting-state functional magnetic resonance imaging analyses on 114 participants to investigate the neural correlates of self-esteem.ResultsWe found that high SE correlated with robust functional connectivity between the left dlPFC and posterior cerebellum. Associations between the left dlPFC and right lingual gyrus, the right vlPFC and insula were FDR-survived, along with diminished connectivity between the left vlPFC, angular gyri, and thalamus.DiscussionThese results not only support our hypothesis regarding the dual role of SE—which includes its social cognitive role in avoiding social exclusion and its emotional resilience in enduring such exclusion—but also suggest a potential link with rumination.